Active bacterial core surveillance of the emerging infections program network. - Schuchat, A (Centers for Disease Control and Prevention, 2001)
Active Bacterial Core surveillance (ABCs) is a collaboration between the Centers for Disease Control and Prevention and several state health departments and universities participating in the Emerging Infections Program Network. ABCs conducts population-based active surveillance, collects isolates, and performs studies of invasive disease caused by Streptococcus pneumoniae, group A and group B Streptococcus, Neisseria meningitidis, and Haemophilus influenzae for a population of 17 to 30 million. These pathogens caused an estimated 97,000 invasive cases, resulting in 10,000 deaths in the United States in 1998. Incidence rates of these pathogens are described. During 1998, 25% of invasive pneumococcal infections in ABCs areas were not susceptible to penicillin, and 13.3% were not susceptible to three classes of antibiotics. In 1998, early-onset group B streptococcal disease had declined by 65% over the previous 6 years. More information on ABCs is available at www.cdc.gov/ncidod/dbmd/abcs. ABCs specimens will soon be available to researchers through an archive.